2016
DOI: 10.1002/eqe.2710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boundary conditions on the out‐of‐plane response of brick masonry walls in buildings with RC slabs

Abstract: SUMMARYIn modern unreinforced masonry buildings with stiff RC slabs, walls of the top floor are most susceptible to out-of-plane failure. The out-of-plane response depends not only on the acceleration demand and wall geometry but also on the static and kinematic boundary conditions of the walls. This paper discusses the influence of these boundary conditions on the out-of-plane response through evaluation of shake table test results and numerical modelling. As a novum, it shows that the in-plane response of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…The boundary conditions at the bottom and the top of the wall have a large effect on the out-of-plane response of unreinforced masonry walls. 43,44 The boundary conditions used in the tests by Doherty et al aimed at representing existing connections between the masonry walls and reinforced concrete floor slabs. 40,41 In this test setup, the position of the vertical reaction force at the ends of the wall results from the contact between the specimen and the testing rig.…”
Section: Modelling Of the Boundary Conditionsmentioning
confidence: 99%
“…The boundary conditions at the bottom and the top of the wall have a large effect on the out-of-plane response of unreinforced masonry walls. 43,44 The boundary conditions used in the tests by Doherty et al aimed at representing existing connections between the masonry walls and reinforced concrete floor slabs. 40,41 In this test setup, the position of the vertical reaction force at the ends of the wall results from the contact between the specimen and the testing rig.…”
Section: Modelling Of the Boundary Conditionsmentioning
confidence: 99%
“…The numerical model consisted in a discrete element model in which the wall was idealised as a single rigid block; the analytical model used for the force-based and displacement-based assessment was a single degree of freedom system with a trilinear force-displacement relationship. 6 Moreover, with respect to Tondelli et al, 26 a refined contact discretisation is herein adopted, which allows covering configurations in which the wall deformability is relatively high. In that parametric study, the force-based and the displacement-based assessment methods were found to be conservative in 99% and 90% of the cases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the planar analysis is unconservative, even when the results along 2 directions are combined, and that 3D analysis is necessary. 2D analysis can only be used for the study of structures that are either constrained to rock in‐plane (like bridges with shear keys in one direction) or rock in‐plane because of their geometrical shape (eg, masonry among others).…”
Section: Wobbling Isolation Of Bridges: Proof Of Concept and Limitatimentioning
confidence: 99%